A Soldier’s Post-Traumatic Stress Disorder in Kevin Power’s The Yellow Birds (Jurnal Pembelajaran Sastra, 2020)
Post-traumatic stress disorder (PTSD) develops in some individuals who have real-life experience with psychological problems such as shocking, scary, or dangerous events (Davison, 2006). This paper aims at uncovering PTSD in Kevin Powers' The Yellow Birds novel that underlies the behavior of the main characters, Private John Bartle. In the context of war, soldiers often face deadly situations in the middle of warfare. This experience is a kind of horrible death, such as the worst experiences that can be made these people vulnerable and psychologically affected, such as psychosis. This research discusses the causes, symptoms, and the impact of PTSD that occur to the Private John Bartle, the main character. The researcher uses the theory of post-traumatic stress disorder development by Gerald C Davison. The results of the analysis show that: (1) The main cause of post-traumatic stress disorder suffered by Bartle is the tragic death of his best friend on the battlefield, the adverse effects of the war occurred recently; (2) The process of re-experiencing the symptoms experienced by the main character of the novel The Yellow Birds began when Bartle finished his service as a service member who served in the Iraq war; (3) The effect of post-traumatic stress disorder was finally found after the post-traumatic stress disorder suffered by Private John Bartle ended his deployment in the Iraq war. For further studies, it is suggested a comprehensive viewpoint in implementing this approach for the new researcher who has been engaging in related fields of post-traumatic stress disorder. The Yellow Birds novel by Kevin Powers can be used as an illustration of how a post-war soldier struggling with his post-traumatic stress disorder when he comes home.